Macroeconomy and consumer sentiment: performance of the Finnish consumer barometer after ten years - Kari Djerf; Kari Takala (Bank of Finland, 1997)
The Finnish Consumer Barometer was introduced in autumn 1987.Data were first collected twice a year and from August 1991 until September 1995 quarterly.After Finland joined the European Union in 1995, the survey was adopted as one member of the Harmonised Consumer Survey of the European Communities.Since October 1995, data have been collected monthly.Performance of the Consumer Barometer has already been evaluated by means of descriptive studies (see Djerf 1990).As the survey matures, it becomes feasible to make a more thorough study on the usefulness of the survey.Here we are, for example, interested in investigating how consumers were able to predict the long-lasting recession of our economy.The consumer confidence index and the five questions used for calculating it are compared to various components of Finnish macroeconomic time series.Additionally, we analyse the coincidence of other common measures (unemployment expectations, inflation expectations, etc.) as well as other, less frequently studied indicators such as the willingness to save and borrow with their possible counterparts in the real economy.It is important to evaluate whether consumer assessments about different economic questions are useful in predicting various macroeconomic variables i.e. we look for the additional information contained in barometer answers.We end by considering the usefulness of various indicators for specific macro-economic behavioural equations.
URN:NBN:fi:bof-20140807439
Keywords: 330; consumer barometer; economic forecasting; causality testing